Pemberdayaan Ibu-ibu PKK melalui Inovasi Produk Kosmetik Alami Berbasis TOGA di Perumahan Green Semesta Semarang - Dyah Palupiningtyas; Krisnawati Setyaningrum Nugraheni; Ambar Dwi Erawati; Yema Charista Zelda; Ani Puspitasari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This community service program aimed to empower women from the Family Welfare Program (PKK) in Green Semesta Housing, Semarang through the innovation of natural cosmetic products based on medicinal plants (TOGA). The